Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.bbmt.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Criteria for Adult Related Donors: A Consensus Statement from the Worldwide Network for Blood and Marrow Transplantation Standing Committee on Donor Issues

Abstract: The number of allogeneic hematopoietic stem cell (HSC) transplants performed globally each year continues to increase. Advances in HLA typing, better supportive care, and administration of reduced-intensity conditioning regimens allow treatment of older patients with older sibling donors. Pretransplant donor assessment and testing are very important processes affecting the quality and safety of donation. For unrelated HSC donors detailed recommendations for health assessment have been published, allowing donat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 66 publications
(74 reference statements)
2
31
0
Order By: Relevance
“…They clarify the role of matching in times when HSCT should provide for each patient a better outcome regarding overall survival, quality of life and costs; 19 they add caution to current concepts to 'find a donor option for every patient. [12][13][14][15][16][17] They fit with recent studies that well-matched unrelated donor HSCT showed results similar to those with matched sibling donors. They suggest complete HLA-typing (12 out of 12 antigens) of unrelated donors 26,27 before decision-making.…”
Section: Alloreactivity In Hsct a Gratwohl Et Alsupporting
confidence: 81%
See 2 more Smart Citations
“…They clarify the role of matching in times when HSCT should provide for each patient a better outcome regarding overall survival, quality of life and costs; 19 they add caution to current concepts to 'find a donor option for every patient. [12][13][14][15][16][17] They fit with recent studies that well-matched unrelated donor HSCT showed results similar to those with matched sibling donors. They suggest complete HLA-typing (12 out of 12 antigens) of unrelated donors 26,27 before decision-making.…”
Section: Alloreactivity In Hsct a Gratwohl Et Alsupporting
confidence: 81%
“…Some early promising results have triggered a rapid expansion in the use of haploidentical donors; still, they await confirmation. [12][13][14][15][16] Recent results from a large EBMT study with high-risk AML patients indicate a similar outcome at 2 years after haploidentical as compared to 10/10 antigen matched unrelated donor transplants. Non-relapse mortality was reported to be higher, relapse incidence to be lower after haploidentical HSCT, 28 follow-up was short and risk profiles of the patients different.…”
Section: Alloreactivity In Hsct a Gratwohl Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The upper age limit of MSD for BM and mobilized PBSC harvest is unclear [54]. In general, increasing recipient age is frequently accompanied by increased donor age in MSDs.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate data regarding RDs is concerning for a number of reasons. Although URD registries have specific guidelines regarding donor clearance [8], there are not generally accepted guidelines about when to reject a RD, although a publication from the Worldwide Network for Blood and Marrow Transplant advocates for transplant centers to adopt standards similar to URD registries [9]. In addition, RDs vary tremendously in age (from infants to individuals in their seventies) and are often willing to donate to family members in spite of significant comorbidities or potentially increased donor risk.…”
Section: Introductionmentioning
confidence: 99%